2015
DOI: 10.1097/ijg.0b013e31829e1b8b
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Association Between Patterns of Eye Drop Prescription and Medication Usage in Glaucoma Subjects

Abstract: Patients with glaucoma who used eye drops incorrectly were routinely prescribed additional bottles of eye drops. Ophthalmologists should determine whether patients who request an unusual number of eye drops are using the eye drops correctly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Results of studies using self-report and objectively assessed eye drop technique have both found high rates of incorrect use (Tables 2 and 4). Patients seem fairly willing to admit that they incorrectly perform eye drop instillation [17,18,20,34]. However, self-report may still be less reliable than more objective measures.…”
Section: Methods Of Assessing Eye Drop Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…Results of studies using self-report and objectively assessed eye drop technique have both found high rates of incorrect use (Tables 2 and 4). Patients seem fairly willing to admit that they incorrectly perform eye drop instillation [17,18,20,34]. However, self-report may still be less reliable than more objective measures.…”
Section: Methods Of Assessing Eye Drop Techniquementioning
confidence: 99%
“…Contaminating the bottle by touching the eye or face was the most frequently missed step. Reported rates of contaminating the bottle in eight different studies ranged from 18.2 [26] to 80% (Table 3) [22,26,17,19,13,23,11 ⬛ ,5,15,9,25,20,14,20]. Two other studies reported separate estimates for touching multiple sites with the bottle; Sleath et al [15] found that 34% of patients touched the eye or eyelash and 52% touched the face, whereas Tatham et al [9] found that 15.3% touched the eye and 27.1% touched the eyelid or lashes.…”
Section: Observational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fixed combination therapy has an advantage with respect to patient adherence in subjects with glaucoma by decreasing the number of eye bottles required. 1 , 2 The effectiveness of this treatment has been shown to be equal to or greater than that of combination therapy. 3 8 Carbonic anhydrase inhibitor and beta-blocker fixed combination therapies are now available in two types: dorzolamide 2% or 1%/timolol 0.5% and brinzolamide 1%/timolol 0.5%.…”
Section: Introductionmentioning
confidence: 99%